Acoustic activity pattern of birds in Ayer Hitam Forest Reserve, Selangor - Lau, Keeny Kin Shoon (2018)
Acoustic method has increasingly being used in the tropics to survey forest birds. This study was conducted to examine bird acoustic activity pattern in relation to distance to forest edge, microclimate factors as well as different survey periods in the Ayer Hitam Forest Reserve, Selangor. Sound recording was made at six transects that were spaced 400m apart and at a distance of 100m, 200m, 300m to 400m from the forest edge. Over a total of 19 days from 10th July to 26th July 2017, 90 different bird species were recorded. A Kruskal-Wallis H test found that there were no significant differences in the number of species recorded at different distances from the forest edge. Results from the Mann-Whitney test showed a significant difference in the number of bird species called in the morning and afternoon. A Spearman correlation test found that there was a significant correlation with respect to the number of bird species recorded and temperature as well as light intensity. Acoustic activities of birds were mostly recorded during the morning session when the temperature and light intensity were low. Results from this study can aid in improving forest bird survey using vocalization in the future.